Is the way to a man's heart through his stomach? Enteropericardial fistula: case series and literature review. Issue 5 (7th June 2012) - Imran Hamid, U.; Booth, K.; McManus, K.
SUMMARY Fistula formation between the pericardium and the gastrointestinal tract is rare. Enteropericardial fistulae may present dramatically, many have prodromal symptoms even though they are not symptoms usually associated with esophageal disease. Prompt diagnosis and expedient surgery can result in survival. We describe three cases of enteropericardial fistulae diagnosed during emergency surgery for sepsis or hemorrhage. All had previous surgery though the details were not available to the operating surgeons because of the time that had passed since their original operation. All three patients survived, albeit with prolonged hospital stay and repeated surgery. A review of the English language literature revealed 95 cases (Table 1). Fifty‐eight had a history of previous surgery, particularly fundoplication or esophagectomy. Ten had advanced malignancy and were treated conservatively. All eight patients with fistulae, which were iatrogenic or due to foreign bodies, survived without aggressive surgery. For more extensive pathology, a successful outcome was achieved in 32 of the 36 cases when the upper gastrointestinal (GI) tract was defunctioned because of the presence of major sepsis or because the healthy vascularized tissue was transposed into the area at risk for further fistula formation. Where less aggressive surgery was performed only 12 of 27 patients survived (P < 0.0001). Esophageal surgeons need to be aware of the late complications and associated atypical symptoms of historical procedures which are no longer in common usage. Where an enteropericardial fistula is present, defunctioning of the upper GI tract or repair with transposition of vascularized tissue gives a better chance of a successful outcome.